If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8 + 3h = 2(h + -5) Reorder the terms: -8 + 3h = 2(-5 + h) -8 + 3h = (-5 * 2 + h * 2) -8 + 3h = (-10 + 2h) Solving -8 + 3h = -10 + 2h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-2h' to each side of the equation. -8 + 3h + -2h = -10 + 2h + -2h Combine like terms: 3h + -2h = 1h -8 + 1h = -10 + 2h + -2h Combine like terms: 2h + -2h = 0 -8 + 1h = -10 + 0 -8 + 1h = -10 Add '8' to each side of the equation. -8 + 8 + 1h = -10 + 8 Combine like terms: -8 + 8 = 0 0 + 1h = -10 + 8 1h = -10 + 8 Combine like terms: -10 + 8 = -2 1h = -2 Divide each side by '1'. h = -2 Simplifying h = -2
| x-5+4x+2=2x-7 | | -4m+4(m+2)=2-6m | | 11-7x=127-35x | | x-279= | | 5x^2-12x+2=0 | | 6-14*4= | | x^2-16x-1=0 | | 0=10+2t+4t | | 6x+6=-120-10x | | 6-14= | | z^2+22+c= | | -7-5x=5x+16 | | 2x+7(3-4)=0 | | 60-2x=7x-8x | | 3(x-6)+2x=22-3x | | 3x+36=12x-36 | | 6f+24=-2f | | (2-x)*3=18 | | X+6=3(4+x) | | 1410-7x=20+23 | | x^2-30x-20=0 | | (-7)+(-20)= | | 8x+2=3x+12 | | 2b+-9=29 | | r^2-2rf-24f^2=0 | | -81-40x=7x+2 | | C=15(3n+8) | | (-5x^2+8)+(8x^2-6x+1)= | | (17x+9)+(8x+13)= | | 12n=6-3p | | 7(1.4+0.8y)-5y=26 | | 40-8v=-7(8v+8) |